A Review on Current Treatment of Multiple Sclerosis Disease - Shinde, Trupti C.; Wagh, Snehal M.; Solanke, Kaustubh B.; Folane, P. N. (Asian Journal of Pharmaceutical Research and Development, 2020)
Multiple sclerosis is a chronic inflammatory disease of the CNS characterized by the demyelination and axonal loss. The incidence of the MS is increasing worldwide. The underlying cause of MS and mechanisms behind this increase remain opaque, although complex gene, environmental interactions almost certainly play a significant role. The epidemiology of MS indicates the low serum level serum level of vitamin D, smoking and childhood obesity are likely to play a role in disease development. Diagnostic criteria have been adapted to facilitate earlier diagnosis with increased sensitivity and specificity.